2023
DOI: 10.1186/s12917-023-03592-6
|View full text |Cite
|
Sign up to set email alerts
|

High-energy diet modify rumen microbial composition and microbial energy metabolism pattern in fattening sheep

Abstract: Higher dietary energy is often used to achieve better animal performance in mutton sheep production. Notably, changing the diet formula affects rumen fermentation and the microbiota of ruminants. In this study, we investigated the effect of dietary energy on rumen fermentation and ruminal microbiota in fattening sheep. Fifteen 2-month-old white-headed Suffolk sheep (♂) × Hu sheep (♀) crossbred lambs were randomly divided into three treatments based on the dietary energy of the feeds fed: 8.67 MJ/kg (Low energy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…In ruminant-related studies, it was found that a high-energy diet increased lipid metabolism in the microbiota. Carbohydrate-activating enzyme (CAZy) genes involved in energy metabolism were upregulated, while genes regulating plant cell wall degradation were downregulated in the high-energy group [76]. This is similar to our findings that microbial involvement in lipid metabolism was significantly greater after high-energy supplementation than in the NSF.…”
Section: Presumptionsupporting
confidence: 89%
“…In ruminant-related studies, it was found that a high-energy diet increased lipid metabolism in the microbiota. Carbohydrate-activating enzyme (CAZy) genes involved in energy metabolism were upregulated, while genes regulating plant cell wall degradation were downregulated in the high-energy group [76]. This is similar to our findings that microbial involvement in lipid metabolism was significantly greater after high-energy supplementation than in the NSF.…”
Section: Presumptionsupporting
confidence: 89%
“…The results indicated a significant increase in species richness of bacterial communities with the addition of DPF, although the Shannon and coverage indices showed no significant differences. At the phylum level, the microbial composition of the rumen is relatively stable, predominantly comprising Firmicutes, Bacteroidota, Fibrobacteres , and Proteobacteria (McCann et al, 2014 ; Deusch et al, 2017 ; Ge et al, 2023 ). In line with previous studies, the rumen microbiota in our study was dominated by Firmicutes and Bacteroidota , collectively accounting for over 90% of the total abundance in each treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…The digestion of more than 70% of carbohydrates and proteins in the feed is completed by rumen microorganisms (Wang et al, 2020 ; Zhang et al, 2021 ). Therefore, diet composition is an important factor affecting the structure and function of rumen microflora (Chai et al, 2021 ; Ge et al, 2023 ). Alpha diversity indexes can reflect the richness and diversity of species in the samples, of which the ACE index and Chao1 index were mainly related to the richness of microbial communities, and the larger the value, which indicates that there were more species in the samples, the higher the richness; whereas the Shannon index and the Simpson index were related to the diversity of microbial communities; the larger the Shannon index, the higher the diversity of microbial communities, and the smaller the Simpson index, the higher the diversity of microbial communities (Jiang et al, 2022 ; Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%